Reliability and psychometric properties of the Greek translation of the State-Trait Anxiety Inventory form Y: Preliminary data - Nimatoudis Ioannis; Bizeli Vasiliki; Papadopoulou Anna; Kleanthous Soula; Papadopoulou Marina; Fountoulakis Konstantinos N; Iacovides Apostolos; Kaprinis George S (Annals of General Psychiatry, 2006)
Abstract Background The State-Trait Anxiety Inventory form Y is a brief self-rating scale for the assessment of state and trait anxiety. The aim of the current preliminary study was to assess the psychometric properties of its Greek translation. Materials and methods 121 healthy volunteers 27.22 ± 10.61 years old, and 22 depressed patients 29.48 ± 9.28 years old entered the study. In 20 of them the instrument was re-applied 1–2 days later. Translation and Back Translation was made. The clinical diagnosis was reached with the SCAN v.2.0 and the IPDE. The Symptoms Rating Scale for Depression and Anxiety (SRSDA) and the EPQ were applied for cross-validation purposes. The Statistical Analysis included the Pearson Correlation Coefficient and the calculation of Cronbach's alpha. Results The State score for healthy subjects was 34.30 ± 10.79 and the Trait score was 36.07 ± 10.47. The respected scores for the depressed patients were 56.22 ± 8.86 and 53.83 ± 10.87. Both State and Trait scores followed the normal distribution in control subjects. Cronbach's alpha was 0.93 for the State and 0.92 for the Trait subscale. The Pearson Correlation Coefficient between State and Trait subscales was 0.79. Both subscales correlated fairly with the anxiety subscale of the SRSDA. Test-retest reliability was excellent, with Pearson coefficient being between 0.75 and 0.98 for individual items and equal to 0.96 for State and 0.98 for Trait. Conclusion The current study provided preliminary evidence concerning the reliability and the validity of the Greek translation of the STAI-form Y. Its properties are generally similar to those reported in the international literature, but further research is necessary.